A randomised controlled trial of Lichtenstein repair with Desarda repair in the management of inguinal hernias. (July 2021) - Jain, Sudhir Kumar; Bhatia, Sushant; Hameed, Tariq; Khan, Rehan; Dua, Amrita
Abstract: Background: Ever since the advent of mesh hernioplasty with low recurrence rates, surgeons have turned a blind eye towards its devastating mesh related complications. Consequently, the quest for the best hernia surgery, that is as effective as the mesh repair but lacks its complications, continues. Objectives: The present study was carried out to compare the results of the Lichtenstein repair with the Desarda repair in the treatment of inguinal hernias. Methods: A total of 77 patients with 87 hernias were randomly allocated into two groups to undergo either the Desarda repair (Group I, 39 patients with 45 hernias) or the Lichtenstein repair (Group II, Control, 38 patients with 42 hernias). 3 patients didn't complete the follow-up and were excluded from analysis. Finally, 40 hernias were analyzed in the Lichtenstein group and 44 in the Desarda group. Results: After a 6-month follow-up period it was found that neither of the two groups had any recurrence. The incidence of chronic inguinodynia was much higher in the Lichtenstein group as compared to Desarda group. The pain scores, mean operating time, mean time to return to work and analgesic requirement was much lower with the Desarda repair as compared to Lichtenstein repair. Conclusion: Desarda repair was found to be as effective as the Lichtenstein repair in terms of recurrence and better in terms of chronic inguinodynia, complications and post operative pain scores. Desarda repair requires a significantly shorter operating time. The economic burden of this repair is much less compared to mesh repair. Highlights: Inguinal hernia remains one of the most commonly performed surgery by general surgeons. There are various techniques but researchers have focused on one with zero recurrence, less complications and less post operative pain. Desarda (tissue repair) is a technique where mesh is not used. It is very promising for countries with low healthcare budget like India. In our study Desarda has been found to have same rate of recurrence as Lichtenstein with less post operative pain (inguinodynia) and infections. Operating time was also less in Desarda repair, along with less requirement of post operative analgesics and early return to routine activities.